Cities trajectories in the digital era: Exploring the impact of technological advancement and institutional quality on environmental and social sustainability. (1st December 2022) - Abid, Nabila; Marchesani, Filippo; Ceci, Federica; Masciarelli, Francesca; Ahmad, Fayyaz
Abstract: Rising environmental and social challenges have compelled policymakers and academicians worldwide to look for an optimal solution to spur cities into a new dimension to meet future needs. In this transition, technological advancement and institution quality has emerged as viable solutions to ensure sustainable city development. However, urban inequality, economic conditions, and institutional quality across cities have produced mixed yet controversial outcomes. By dividing the Italian cities into three economic levels, this article uncovers the relationship between technological advancement, institutional quality, and environmental and social sustainability using data from 2010 to 2019. The GLS model results show that a city's economic development rate significantly influences the potential impact of technological advancement and institutions on environmental and social sustainability, also suggesting that technological advancement is associated with environmental and social sustainability in the longer run. At the same time, institutional quality is not an effective variable in the Italian context. The results produce policy and academic implications concerning the current trend in the institutional capacity to ensure environmental and social sustainability and support the current debate concerning the role of technological advancement in cities in supporting environmental conditions and socially sustainable societies.